Assessment of Natural Radioactivity and Associated Radiation Hazards in Soils samples from Khammuane Provine, Laos - Leuangtakoun, Somsavath; Loat, Bui Van; Hong, Bui Thi; Duc Thang, Duong; Singsoupho, Sounthone (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: In order to assessment of Natural Radioactivity and Associated Radiation Hazards in soil samples, activity concentration of naturally occurring radionuclides was measured by using a gamma spectrometer with a high energy resolution HPGe detector. The average radioactivity concentrations of 226 Ra, 232 Th and 40 K in the surface layers (5‑30 cm depth) collected from Khammuan province, Laos, were 32.57± 3.35 Bq.kg -1 ,41.10±3.04 Bq.kg -1 and 295.07± 17.36 Bq.kg -1 respectively. From the activity concentration of 226 Ra, 232 Th and 40 K, we derived the parameters using the assessment of the radiological hazard from exposure to these soil samples. The average absorbed dose rate of all measured samples is 52.02±4.09nGy.h -1 , while the average annual effective dose in the outdoor due to gamma radioactivity is found to be (0.060±0.005) mSv.y -1 .The average values for radium equivalent activity, external and internal hazard indices were found to be (114.07± 4.70) Bq.kg -1 , (0.31± 0.02) and (0.39± 0.03) respectively. Keywords: Natural radionuclides, Radium Equivalent Activity, Absorbed gamma dose rate, Annual effective dose rate, Khammuan province. References [1] United Nations Scientific Committee on the Effects of Atomic Radiation. Sources and effects of ionizing radiation, Report to the General Assembly with Scientific Annexes, Vol. 1. Annex B Exposure from natural radiation sources, United Nations. UNSCEAR(2000). www.unscear.org/docs/reports/annexb.pdf [2] P.E, Abiama, P.O. Ateba, G. H. Ben-Bolie, H.P. Ekobena, T.El. Khoukhi, High Background Radiation Investigested gamma Spectrometry of the soil in South western of Cameroon, Environment Radioactivity 1 (2010), 739-743. DOI:10.1016/j.jenvrad.2010.04.017 [3] K.M. Thabayneh, M.M. Jazzar, Natural radioactivity levels and estimation of radiation exposure in environmental soil samples from Tulkarem Province Palestine, Open J. Soil Sci. 2 (2012) 7-16. http://dx.doi.org/10.4236/ojss.2012.21002. [4] N.Q. Huy et al., Natural radioactivity and external does assessment of surface soils in Vietnam, Radiation Protection Dosimetry 151 (3) (2012) 522–531. doi:10.1093/rpd/ncs033. [5] F.S. Erees, S. Aközcan, Y. Parlak, S. Çam, Assessment of dose rates around Manisa (Turkey), Radiat Measure 41(2006) 598‑601. https://doi.org/10.1016/j.radmeas.2005.11.004. [6] UNSCEAR, United Nations Scientific Committee on the Effects of Atomic Radiation. Ionizing Radiation Sources and Biological Effects, Reports to general assembly, United Nations, New York, 1993. [7] A. El-Taher, INAA and DNAA for uranium determination in geological samples from Egypt, Applied Radiationand Isotopes 68 (6) (2010) 1189–1192. [8] J. Beretka, P.J. Mathew, Natural Radioactivity of Australian Building Materials, Industrial Wastes and by-Products, Health Physics 48 (1) (1985) 87-95. doi:10.1097/00004032-198501000-00007. [9] K. Prasong, A. Susaira, Natural radioactivity measurements in soil samples collected from municipal area of Hat Yai District in Songkhla province, Thailand. KMITL Sci. J. 8 (2 ) (2008) 52-58. [10] M. Musa, Z. Hamzah, A.Saat, Measurement of natural radionuclides in the soil of Highland agricultural farm and in Proceeding of the 3rdInternational Symposium and Exhibition in Subtainable Energy and invironment (ISESEE’11) IEEE, Melaka, Malaysia, (2011) 172-176. [11] S. Leuangtakoun, B.V. Loat, V.T.K. Duyen, K.N. Khang, Natural Radioactivity and External Dose Assessment of Surface Soil in Bolikhamxay Province, Laos, VNU Journal of Science: Mathematics of Physics 33 (4) (2017) 10-16. https//doi.org/ 10.25073/2588-1124/vnumap.4224.